Adubação com biofertilizante misto no desenvolvimento da cenoura cv. Brasília em duas condições de ambiente na região do Maciço de Baturité - Terto, Rennan Salviano (2019)
The carrot is a vegetable consumed worldwide, because of its nutritional value. However, it develops in a productive system the basis of chemical inputs responsible for negative impacts on human beings and the environment. Therefore, it emerges the need for the use of techniques for an environmentally healthy and economically sustainable cultivation. Thus, the objective of this study was to evaluate the effect of the application of mixed biofertilizer doses in two cycles and cultivation environments, on soil fertility, in the production and postharvest quality of the carrot, cultivar Brasília. The experiment was carried out at the experimental farm of the International University of Lusofonia Afro-Brasileira (UNILAB), located in Sítio Piroás, municipality of Redenção. The experimental design was in randomized complete blocks in the split-plot scheme, with four blocks. The plots consisted of two cultivation environments (open and under-roofed field) and the subplots for five doses of the mixed biofertilizer (0, 300, 600, 900 and 1,200 mL plant-1 week-1). The data analysis was in subdivided plots at the end of the cultivation cycles, as well as for the fertility of the substrate analyzed at the beginning and at the end of each productive cycle from the treatments applied. The levels of N, P, K and MO were determined. The production and post-harvest variables analyzed were: mean root diameter, mean root length, mean root weight, yield, total titratable acidity, pH and soluble solids. The second cycle of cultivation and the application of biofertilizer in different doses provided nutritional increment to the substrate by the increasing linear adjustment of the regression models. However, the levels of N and MO were lower than those obtained for the first crop cycle. The interaction cycle and environment showed significance only for the variables mean root weight, productivity and titratable acidity. The exception of the soluble solids the other post-harvest variables and the production were significant the application of the biofertilizer throughout the cycles. The open-field cultivation and the application of biofertilizer in different doses provided answers only in the production variables, except for the average root length. The average experimental yield estimated for a stand of 84,602.37 plants was 5.82 t ha-1 (first cycle) and 8.86 t ha-1 (second cycle). Biofertilizer had a positive effect during the cultivation cycles through the nutritional increment to the substrate in relation to the initial condition.